Effects of basalt, concrete fines, and steel slag on maize growth and toxic trace element accumulation in an enhanced weathering experiment - J. Rijnders; A. Vienne; S. Vicca (Biogeosciences)
Terrestrial enhanced silicate weathering is a CO2 removal technology involving the application of ground silicate materials to agricultural soils. Next to its CO2 removal potential, it can improve soil fertility and crop growth, but silicate materials can also contain toxic trace elements. In a mesocosm experiment, we investigated the effect of basalt, concrete fines, and steel slag on biomass, nutrients, and the toxic trace element concentration of Zea mays, using a dose–response approach.